2011
DOI: 10.1093/jjco/hyr164
|View full text |Cite
|
Sign up to set email alerts
|

Number of Lymph Nodes Retrieved is an Important Determinant of Survival of Patients with Stage II and Stage III Colorectal Cancer

Abstract: Objective: The number of lymph nodes retrieved is recognized to be a prognostic factor of Stage II colorectal cancer. However, the prognostic significance of the number of lymph nodes retrieved in Stage III colorectal cancer remains controversial. Methods: The relationship between the number of lymph nodes retrieved and clinical and pathological factors, and significance of the number of lymph nodes retrieved for prognosis of Stage II and III colorectal cancer were investigated. A total of 16 865 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 25 publications
3
43
0
Order By: Relevance
“…In this study, LNY had an independent prognostic influence in Stage I-III CRC but not Stage IV CRC, as shown in Table IV and Figure 5. This confirms previous findings in Stage II-III colon cancer [15-17,37,] [44][45][46][47] but there is currently no explanation for this phenomenon. One possibility is that a stronger host anti-tumor immune response results in larger regional LNs that are detected more easily [48].…”
Section: Factors Influencing Lny and Survival In Crcsupporting
confidence: 90%
“…In this study, LNY had an independent prognostic influence in Stage I-III CRC but not Stage IV CRC, as shown in Table IV and Figure 5. This confirms previous findings in Stage II-III colon cancer [15-17,37,] [44][45][46][47] but there is currently no explanation for this phenomenon. One possibility is that a stronger host anti-tumor immune response results in larger regional LNs that are detected more easily [48].…”
Section: Factors Influencing Lny and Survival In Crcsupporting
confidence: 90%
“…However, in colorectal cancer, apart from patients with distal metastasis (stage IV), all node-positive patients are categorized as stage III regardless of their T status based on the TNM classification [5]. Although lymph node status has been identified as an essential prognostic factor in colorectal cancer that can guide adjuvant therapy and evaluate prognosis [22, 23], the integration of TN categories into a cancer staging system remains complicated. Therefore, the over-estimated weighting of node metastasis in the current AJCC cancer staging system leads to poor monotonicity of gradients from the early to the advanced cancer stages in colorectal cancer [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node (LN) status is the single most important predictor of survival in nonmetastatic colorectal cancer . Multiple studies have demonstrated a relationship between the number of LNs retrieved during colectomy and survival . Although the American Joint Committee on Cancer (AJCC) recommends a minimum of 12 nodes for adequate staging, an optimal cutoff has yet to be established .…”
Section: Introductionmentioning
confidence: 99%